Story and Recall in First-Person Shooters. (11th March 2008) - Pinchbeck, Dan
Abstract : Story has traditionally been seen as something separate to gameplay—frequently relegated to an afterthought or epiphenomenon. Nevertheless, in the FPS genre there has been something of a renaissance in the notion of the story-driven title. Partially, this is due to advances in technology enabling a greater capacity for distributed storytelling and a better integration of story and gameplay. However, what has been underrecognised is the dynamic, epistemological, and psychological impact of story and story elements upon player behaviour. It is argued here that there is evidence that story may have a direct influence upon cognitive operations. Specifically, evidence is presented that it appears to demonstrate that games with highly visible, detailed stories may assist players in recalling and ordering their experiences. If story does, indeed, have a more direct influence, then it is clearly a more powerful and immediate tool in game design than either simply reward system or golden thread.